The Influence of Demographic and Family Characterristics on Learning Outcome of Vietnamese and Eastern Asian Students (PISA 2015 Results) - Huong, Vu Thi (VNU Journal of Science: Education Research; Vol 37 No 1DO - 10.25073/2588-1159/vnuer.4498, 2021)
This paper tests the hypothesis proposed in the research framework on the influence of demographic and family characteristics on learning outcome of Vietnamese and Eastern Asian students using the 2015 Programme for International Student Assessment (PISA) data. The research result demonstrates that among the demographic characteristics, no-kindergarten attendance, under-one-year kindergarten attendance or late primary school enrolment could all reduce students’ learning outcome; and among the family characteristics, the socio-economic condition was highly likely to have positive influence on students’ learning outcome. The paper also indicates that Vietnamese students tend to achieve higher learning outcome than that of Eastern Asian students.